Genomic and transcriptomic analyses of Phytophthora cinnamomi reveal complex genome architecture, expansion of pathogenicity factors, and host-dependent gene expression profiles - Shands, Aidan C.; Xu, Guangyuan; Belisle, Rodger J.; Seifbarghi, Shirin; Jackson, Natasha; Bombarely, Aureliano; Cano, Liliana M.; Manosalva, Patricia M. (Frontiers in Microbiology, 2024)
Phytophthora cinnamomi is a hemibiotrophic oomycete causing Phytophthora root rot in over 5,000 plant species, threatening natural ecosystems, forestry, and agriculture. Genomic studies of P. cinnamomi are limited compared to other Phytophthora spp. despite the importance of this destructive and highly invasive pathogen. The genome of two genetically and phenotypically distinct P. cinnamomi isolates collected from avocado orchards in California were sequenced using PacBio and Illumina sequencing. Genome sizes were estimated by flow cytometry and assembled de novo to 140 to 141 Mb genomes with 21,111 to 21,402 gene models. Genome analyses revealed that both isolates exhibited complex heterozygous genomes fitting the two-speed genome model. The more virulent isolate encodes a larger secretome and more RXLR effectors when compared to the less virulent isolate. Transcriptome analysis after P. cinnamomi infection in Arabidopsis thaliana, Nicotiana benthamiana, and Persea americana de Mill (avocado) showed that this pathogen deploys common gene repertoires in all hosts and host-specific subsets, especially among effectors. Overall, our results suggested that clonal P. cinnamomi isolates employ similar strategies as other Phytophthora spp. to increase phenotypic diversity (eg, polyploidization, gene duplications, and a bipartite genome architecture) to cope with environmental changes. Our study also provides insights into common and host-specific P. cinnamomi infection strategies and may serve as a method for narrowing and selecting key candidate effectors for functional studies to determine their contributions to plant resistance or susceptibility.